(untitled) (Journal of the College of Languages (JCL), 2015)
Irak Türkmen edebiyatının divan şiirlerinde büyük simalardan sayılan , ve Irak Türklerinin en içli şairi olan Osman Mazlum .Şiirleri yalnızlık hem ve kederle dolu olan şairin , her zaman büyük bir üzüntüye kablandığı için bunun tüm şiirlerinde yansıtmıştır . Her zaman kaderden şikayetci olan şiirlerinde (Mazlum) mahlasını kullanmıştır . Şairin klasik edebiyatında önemli bir yeri vardır . Hoyrat yoluyla edebiyata giren mazlum’un gönül yarası bu aşıkla dolunca feyizlenmeye ve türlü nağmelerle seslenmeğe başladı . İşte bu güne kadar yazmış olduğu şiirler o sesler hep ahang , terennüm ve tesavırıdır . Bende bu araştırmada ilk önce şairin hayatına , edebi kişiliğine ve eserlerine baş vurduktan sonra şairin kötümserlik ve acı duygularını da osmanlı şiirleriyle ve hoyratlarıyla yeni Türkçeye çevirerekaçıkladım . Son olarak bu araştırmanın okuyucularına yararlı olmasını dilerim . Abstract Ottman belonges to the approach of melancholy in the modern Turkish poetry. He complained his miserable luck ,which accompanied him along his life. And he descended from great ancestries. He was born in 1922 in Kirkuk. His parents are Turkish, his father belonges to the Turkmen tribe Al-Biat. He entered Al-Kuttab (before school), and then he entered the primary school till finishing his high school. Then he joined college of law and he got his Bachelor in arts in 1956 .He worked in offices of ministry of Justice and then he retired. Madhalom faced misteries and agonies in his academic, workable life, and other thing. He didn’t get the benefit of his bachelor in Law. The poet didn’t achieve his goals and expectations in spite of his certification, knowledge, and honesty. He worked in agriculture and other jobs, but he was disappointed at every times. Accordingly, his writing was influenced by his pessimistic point of view. Sometimes his disappointment became firstly and deprived him of fulfilling his wishes, and in other times it pulled him back. In Turkish literature, Madhalom considered as the last poet who used prosody in the language of court. He longed for Arabic prosody. He announced that in spite of prosody difficulty,t it was the best model for poetry. In addition to his poetry , he was distinguished by writing Al-Kwareet which included Proverbs, wise sayings, and Ghazal. And he was the only one who joined Al-Kwareet to national meanings. He regarded as the poet of hopelessness and despair as much as the poet of home and society and this we can see in his poetry as well as in his chaste poems. In Al-Ghazal poems, he revealed the feelings of a lover and be contrastive of choosing rhetorical words and added an aesthetic touch. Then the poem be in touch with the heart and affecting. The research deals with pessimistic feelings in addition to the poets’ life, literary personality, and his poetry of Ghazal. The researcher transformed his poems and hıs Khouairat from the Ottoman language to the modern Turkish in Latin .